A Facile, Eco-friendly, Proton Donor-Acceptor Catalyzed, One-Pot, Three-Component Synthesis of Tetrahydrobenzo[b]pyrans - Indrasena, A.; Riyaz, Sd.; Naidu, A.; Dubey, P.K. (Asian Journal of Chemistry, 2014)
Piperidinium acetate catalyzed, three-component cyclocondensation between aryl aldehydes (1), malononitrile (2) and cyclic-1,3-diketo compounds (3) in the eco-friendly and universal solvent water at room temperature for 0.5 h, resulted in the formation of tetrahydro[b]pyran derivatives (4). The formation of 4 could also be established in a step-wise fashion by isolating independently each of the intermediates benzylidine malononitrile 5 and benzylidine cyclohexane-1,3-dione 6 and treating them subsequently with 3 and 2, respectively to obtain benzopyrans 4. Mechanistic studies on the formation of 4 from 1, 2 and 3 are reported. Further, the synthesis of 4 could also be achieved in two variable but identical end-product giving tandem syntheses by treating 1 with 2 and then with 3 giving 4 or by treating 1 with 3 and then with 2 giving 4. All the products were suitably characterized using NMR, IR and Mass spectroscopy.